The Effect of Work Environment, Workload, and Compensation on Job Satisfaction of Nasmoco Youth Car Benkel Employees - Auriantika Auriantika; Mirwan Surya Perdhana (Universitas Negeri Semarang, 2023)
The purpose of this study is to know and analyze the effect of the work environment on job satisfaction, to know and analyze the effect of workload on job satisfaction, and to know and analyze the effect of compensation on job satisfaction in employees of the Nasmoco Youth car workshop. The technique used in this study is quantitative research method. The number of samples to be taken by researchers is all employees of Benkel Mobil Nasmoco Pemuda totaling 120 employees with saturated samoel retrieval techniques. The data collection technique used in this study used questionnaires. The results of research and analysis that have been carried out are, it is known that the work environment has a positive and significant influence on the job satisfaction of Benkel Mobil Nasmoco Youth employees. It is known that the workload of work has a negative and significant influence on the job satisfaction of Benkel Mobil Nasmoco Youth employees. It is known that compensation has a positive and significant influence on employee job satisfaction of Benkel Mobil Nasmoco Youth employees.